Role of the Lateral Ankle Ligaments in the Vertical Stability of the Fibula. Issue 2 (April 2022) - Filippi, Jorge; Gutierrez, Paulina; Silvestre, Rony A.; Bastias, Gonzalo F.; Morales, Jose Ignacio Quezada; Melo, Rodrigo; Munoz, Gerardo; Cuchacovich Mikenberg, Natalio R.
Category: Basic Sciences/Biologics; Ankle; Trauma Introduction/Purpose: In unstable ankle fractures, syndesmosis and the deltoid ligament have been widely studied, and their importance in their pathophysiology and treatment is recognized. This is not the case of the ankle lateral ligaments, and in particular, their role in the vertical stability of the fibula is unknown. Given their anatomical position, they should avoid proximal translation of the distal fragment of the fibula fracture. Purpose: To quantify the superior translation of the fibula by applying a constant proximal traction force as the syndesmosis and lateral ankle ligaments are sectioned sequentially. Methods: Eleven human ankle cadaveric specimens were used (6 female, 5 male). Removal of the skin and muscles was performed down to the ankle level, preserving the interosseous membrane (IOM). A deep dissection was performed to identify the inferior tibiofibular ligaments and the lateral ligaments of the ankle. Each piece was mounted on a platform specially designed for this work (fig 1), fixing the foot with an axial load of 25 kg, and a proximal traction force of 50 N was applied to the fibula. The syndesmotic ligaments, IOM, anterior talofibular ligaments (ATFL), and calcaneofibular ligament (CFL) were sequentially sectioned. The proximal displacement of the fibula was measured after each sequential section. Normality analysis was performed with the Kolmogorov-Smirnov and Shapiro-Wilkins tests. Differences between groups were evaluated with the ANOVA test with Dunnett and Newman-Keuls post-test. Results: When applying 50 N of proximal traction, the proximal and vertical displacement of the fibula was as follows; no sectioning 1.96 +- 1.19 mm, syndesmosis/IOM sectioning 3.96 +- 1.33 mm, ATFL sectioning 5.9 +- 1.73 mm and 10.2 +- 2.76 mm after sectioning the CFL. Normal distribution was observed in all groups. All measurements had a statistically significant difference between each group (p <0.05). Conclusion: In this model, a complete syndesmosis/IOM lesion produces a mean fibular proximal displacement of 3.96 mm. By adding the ATFL and CFL complete injury, it reaches 10.2 mm. Clinical relevance: In an unstable ankle dislocation with a significant fibular proximal displacement, there is probably a severe compromise of the lateral ligament complex, which could have clinical relevance as it is part of the bone and ligamentary stability ring of the ankle. This is the first study that describes the role of the lateral ligament complex in fibular vertical stability.